Ribeirao Preto/Sp: From Vila Sao Sebastiao Of The Ribeirao Preto To Fragmented Middle-Size City (1850 - 2020) - Silgueiro-dos Santos, Felipe Cesar Augusto [UNESP] (Univ Industrial Santander, 2022)
This article aims to present the process of expansion and urban evolution of the middle city of Ribeirao Preto/SP located in the State of Sao Paulo, Brazil. Through an analysis of the history of formation of this city, we seek to present elements that can demonstrate how it expanded, structured and configures itself as an important city in the Brazilian urban network. From its rural structure to its fragmentary configuration, it is possible to indicate that Ribeirao Preto/SP had its structuring based on the agricultural sector, the same that benefited it in its formation and still does in its current configuration, but currently this medium city is more specialized and spatialized.
Keywords: History; Urbanization; Brazil